Windows 7 Made Simple - Otnes, Kevin; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Windows 7 is more than an operating system. It$1 (Bs your gateway to email, the Web, work, entertainment, and fun. The latest Windows makes your computer more fun, easy, and powerful to use than ever before. With Windows 7 Made Simple, you can unlock the potential and power of Microsoft's latest operating system. Get up and running quickly with the Quick Start Guide Find what you want to know quickly, and learn at your own pace Read AND see how to do it with handy step-by-step visual aidss
Keywords: Computer science; Computer Science; Computer Science, general